The relationship between TP53 Gene Mutation with treatment results in High-Grade Gliomas - Bac Thanh Nguyen; Duc Anh Tran; Hung Quang Ngo; Trung Hoang Nguyen; Hoa Khanh Ngo (Revista Cubana de Medicina Militar)
Introduction: Determining the relationship between TP53 gene mutation and treatment outcome in high-grade gliomas patients has great significance for disease prognosis and treatment outcome monitoring. Ojectives: To determine the relationship between TP53 gene mutation rate and some characteristics of treatment outcome in high-grade gliomas patients. Methods: The study was conducted by descriptive method, on 52 high-grade gliomas patients at Vietnam National Cancer Hospital, from January 2019 to December 2020. Based on statistics of clinical symptoms, paraclinical tests and post-operative monitoring results, it was evaluated the relationship between TP53 gene mutation in study patients with response to treatment and patient's survival time. Results: There was a relationship between TP53 gene mutation and response to treatment according to Response Evaluation Criteria In Solid Tumors (p= 0.004). Progression-free survival was higher in the group with the TP53 mutation than in the group without the TP53 mutation (χ2= 6.7; p= 0.010). The overall survival in the group with the TP53 mutation was higher than the overall survival in the group without the TP53 mutation (χ2= 2.6; p= 0.107). Conclusion: There is a relationship between the occurrence of TP53 gene mutations with treatment response criteria and progression-free survival in patients with high-grade gliomas.